Concentrations and Sources of Arsenic and Fluoride in High-Temperature Geothermal Water from Yangbajing, Xizang - Geng XU; Fangjing XIAO; Xiaomei CUI; Duo BU; Qiangying ZHANG (Yankuang ceshi)
Arsenic (As) and fluoride (F) are two typical harmful elements with high concentrations in Yangbajing high-temperature geothermal water, and the release of As and F from geothermal sources to the surface or near-surface environment can be further promoted and accelerated through geothermal development, causing surface water and soil environmental pollution. To understand the enrichment mechanism of As and F in the geothermal water body, hydrochemical characteristics as well as the concentrations of As and F were investigated by water quality analyzer, atomic fluorescence spectrometry, X-ray fluorescence spectrometry, and ion selective electrode method. The results indicate that the main sources of As and F in geothermal water and surface soil are water-rock leaching interaction. Unique hydrochemical characteristics (Na-HCO3∙Cl) with high concentration Na+ (reach to 445.5mg/L), poor in Ca2+ (as low as 3.31mg/L), and high pH (7.87−9.42) provided a favourable condition for the leaching of As and F in water. Affected by water vapor evaporation, the concentrations of As and F in hot spring water were higher than those in geothermal water and reached 6.50mg/L and 17.89mg/L, respectively. Notably, the total concentrations of As and F in waters were significantly higher than the maximum allowable emission concentrations for harmful components (0.5mg/L for As, and 10mg/L for F) in the Geothermal Resources Assessment Method (DZ40—85). Moreover, the concentrations of total As and F in the soils were 79.50−99.08mg/kg and 1162.70−1285.10mg/kg, respectively, significantly higher than the background values in Xizang soil. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202310260168.